Representation of Frost Full and Compact Proposition in the Russian Language - Bunin Yelets State University, Olga A. Selemeneva, (Opción, 2019)
The authors distinguishes and describes sign clusters which represent a full or a compact proposition of frost in the Russian language on the material of fictional prose. Situational and semantic-cognitive approaches, descriptive-analytical, distributive, and synchronous-diachronic methods were used to interpret the factual data. It was found that, first, the complex signs of the full proposition state of the frost can be expressed through six structural patterns. Second, the compact proposition frost is represented with word combinations and word forms that bear additional meanings of time and reason. Third, in all polypropositional statements the compact proposition can be explicated.